Chennakeshava temple, Beluru, Garuda at the pillar facing the east entrance - image 2 - Bharath M (2021)
In the Chennakeshava temple placed at the foot of the Dhvaja-sthamba is a sculpture of the divine bird Garuda, who is part bird and part human and is the mount of God Vishnu.